Chemically-induced osteogenic cells for bone tissue engineering and disease modeling. (October 2022) - Yoon, Ji-Young; Mandakhbayar, Nandin; Hyun, Jeongeun; Yoon, Dong Suk; Patel, Kapil D.; Kang, Keunsoo; Shim, Ho-Shup; Lee, Hae-Hyoung; Lee, Jung-Hwan; Leong, Kam W.; Kim, Hae-Won
Abstract: Cell reprogramming can satisfy the demands of obtaining specific cell types for applications such as tissue regeneration and disease modeling. Here we report the reprogramming of human fibroblasts to produce chemically-induced osteogenic cells (ciOG), and explore the potential uses of ciOG in bone repair and disease treatment. A chemical cocktail of RepSox, forskolin, and phenamil was used for osteogenic induction of fibroblasts by activation of RUNX2 expression. Following a maturation, the cells differentiated toward an osteoblast phenotype that produced mineralized nodules. Bulk and single-cell RNA sequencing identified a distinct ciOG population. ciOG formed mineralized tissue in an ectopic site of immunodeficiency mice, unlike the original fibroblasts. Osteogenic reprogramming was modulated under engineered culture substrates. When generated on a nanofiber substrate ciOG accelerated bone matrix formation in a calvarial defect, indicating that the engineered biomaterial promotes the osteogenic capacity of ciOG in vivo . Furthermore, the ciOG platform recapitulated the genetic bone diseases Proteus syndrome and osteogenesis imperfecta, allowing candidate drug testing. The reprogramming of human fibroblasts into osteogenic cells with a chemical cocktail thus provides a source of specialized cells for use in bone tissue engineering and disease modeling.